Нужно воспользоваться формулой разности квадратов практически во всех примерах: (a - b)(a + b) = a² - b².
Выполните умножение:
1) 5b(b - 1)(b + 1) = 5b(b² - 1) = 5b³ - 5b;
2) (c + 2)(c - 2) · 8c² = (c² - 4) · 8c² = 8c⁴ - 32c²;
3) (m - 10)(m² + 100)(m + 10) = (m - 10)(m + 10)(m² + 100) =
= (m² - 100)(m² + 100) = m⁴ - 10 000;
4) (a² + 1)(a² - 1)(a⁴ + 1) = (a⁴ - 1)(a⁴ + 1) = a⁸ - 1;
Упростите выражение:
1) (x + 1)(x - 1) - (x + 5)(x - 5) + (x + 1)(x - 5) = x² - 1 - (x² - 25) + x² - 5x + x - 5 = x² - 1 - x² + 25 + x² - 4x - 5 = x² - 4x + 19;
2) 81a⁸ - (3a² - b³)(9a⁴ + b⁶)(3a² + b³) = 81a⁸ - (3a² - b³)(3a² + b³)(9a⁴ + b⁶) = 81a⁸ - (9a⁴ - b⁶)(9a⁴ + b⁶) = 81a⁸ - (81a⁸ - b¹²) = 81a⁸ - 81a⁸ + b¹² = b¹².
Объяснение:
1)х^2+10x+25
2)4x^2+36x+81
3)c^2-12c+36
4)9a^2-12a+4
5)(c-1)(c+1)
6)x^4+4x^2y^2+4y^4
7)x^2+14x+49
8)64x^2+48x+9
9)x^2-22x+121
10)4x^2-24x+36
11)4a^4+4a^2b^2+b^4
12)16p^2-8pt^2+t^4